HEMATOLOGIC MODIFICATIONS IN UNIVERSITY WOMEN DURING MENSTRUAL FLOW AND INFLUENCE IN PERFORMANCE (Fiep Bulletin - online, 2014)
Abnormalities in the menstruation cycle (MC) are commons in adolescents and young women are physical practicing or not. The effect caused for the phases of the MC in the performance in exercises have been studied and many information are Known. However, we know just a little about the effect of exercises related to menstrual flow (MF) in that says respect to the blood elements and the consequences related to exercises. The objective of the present study is to verify modifications in blood composition in function of the MF in universities women in physically activity. A group (n=6) composed for universities women, was monitored by five months by a specific questionnaire and had carried through a training for 12 weeks of physical exercises. The blood collection occurred in first day and the mid-day of the MF. Occurred diminishes in number of white blood cells in a proportion of 4/6 and in number of plaquelets of 3/3. Didn't a pattern blood modification in variables analyzed. The performance in exercises not be related with blood modifications provoked by the FM or with the phase of the MF.